In Situ Evaluation of Cr(VI) Bioavailability and Rhizosphere Effects in Reduced Cr-Contaminated Soil Based on Diffusive Gradients in Thin Films Technique - Liu, Zhaodong; Wang, Haicui; Li, Yan; Wang, Guifeng; Jing, Yongping; Bo, Luji; Zhong, Ziwen; Zhang, Hanlin; Wang, Yanqin (Geomicrobiology journal, 2024)
The transformation between Cr(III) and Cr(VI) occurs in Cr-contaminated soil, which can be regulated by root-soil interactions, under natural conditions. In situ investigation of the effectiveness of different reductants in reducing Cr(VI) to Cr(III), and thereby the reoccurrence risk in reduced Cr-contaminated soil, can improve the understanding of Cr biogeochemistry and toxicity. Traditional and high-resolution diffusive gradients in thin films (DGT) were used to measure Cr(VI) availability and rhizosphere effect controlling the chemical behaviors of Cr(VI) in the rice rhizosphere microdomain. The Cr(VI) concentration in the soil solution (C soln ) of the rhizosphere region varied according to the reductant type and followed the order: Molasses > CaS 4 >Fe(II). Rice root activity increased the C soln in the rhizosphere region by 2.16 μg/L, 1.90 μg/L, and 1.08 μg/L for Fe(II), CaS 4 , and Molasses treatments, respectively. The Cr(VI) concentration measured by DGT (C DGT ) in the reduced Cr-contaminated soils increased from 0.96-1.17 μg/L in the bulk region to 1.23-1.76 μg/L in rhizosphere region. The variation in the effective concentration of Cr(VI) (C E ) was similar to that of C soln in the rice rhizosphere microdomain. C soln accounted for 14.71-19.36% of the C E , further suggesting that bioavailable Cr(VI) mainly originated from the replenishment from the solid phase. The sequence of the average Cr(VI) flux in the reduced Cr-contaminated soil was Molasses, CaS 4 , and Fe(II). Except for Molasses, there was no obvious Cr(III) in Fe(II) and CaS 4 . For Fe(II), a higher phosphate flux in the rhizosphere microdomain hindered Cr(VI) uptake. High-resolution imaging provides a theoretical basis for the bioavailability evaluation and remediation of Cr-contaminated soil. Compared with CaS 4 and Molasses, Fe(II) was the most effective reductant for remediating Cr-contaminated soils.